Comparison of Myelin-Associated Glycoprotein With Vincristine for Facial Nerve Inhibition After Bilateral Axotomy in a Transgenic Thy1-Gfp Rat Model - Ali, S. Ahmed (JAMA Facial Plast Surg, 2019)
IMPORTANCE: Aberrant synkinetic movement after facial nerve injury can lead to prominent facial asymmetry and resultant psychological distress. The current practices of neuroinhibition to promote greater facial symmetry are often temporary in nature and require repeated procedures. OBJECTIVE: To determine whether myelin-associated glycoprotein (MAG), a specific neuroinhibitor, can prevent neuroregeneration with efficacy comparable with that of vincristine, a well-established neurotoxin. DESIGN, SETTING, AND PARTICIPANTS: Rats transgenic for Thy-1 cell surface antigen–green fluorescent protein (Thy1-Gfp) were randomized into 3 groups. Each rat received bilateral crush axotomy injuries to the buccal and marginal mandibular branches of the facial nerves. The animals received intraneural injection of saline, MAG, or vincristine. MAIN OUTCOMES AND MEASURES: The animals were imaged via fluorescent microscopy at weeks 1, 3, 4, and 5 after surgery. Quantitative fluorescent data were generated as mean intensities of nerve segments proximal and distal to the axotomy site. Electrophysiological analysis, via measurement of compound muscle action potentials, was performed at weeks 0, 3, 4, and 5 after surgery. RESULTS: A total of 12 rats were included in the study. Administration of MAG significantly reduced fluorescent intensity of the distal nerve in comparison with the control group at week 3 (mean [SD], MAG group: 94 [11] intensity units vs control group: 130 [11] intensity units; P < .001), week 4 (MAG group: 81 [19] intensity units vs control group: 103 [9] intensity units; P = .004), and week 5 (MAG group: 76 [10] intensity units vs control group: 94 [10] intensity units; P < .001). In addition, rats treated with MAG had greater fluorescent intensity than those treated with vincristine at week 3 (mean [SD], MAG group: 94 [11] intensity units vs vincristine group: 76 [6] intensity units; P = .03), although there was no significant difference for weeks 4 and 5. At week 5, both MAG and vincristine demonstrated lower distal nerve to proximal nerve intensity ratios than the control group (control group, 0.94; vs MAG group, 0.82; P = .01; vs vincristine group; 0.77; P < .001). There was no significant difference in amplitude between the experimental groups at week 5 of electrophysiological testing. CONCLUSIONS AND RELEVANCE: Lower facial asymmetry and synkinesis are common persistent concerns to patients after facial nerve injury. Using the Thy1-Gfp rat, this study demonstrates effective inhibition of neuroregeneration via intraneural application of MAG in a crush axotomy model, comparable with results with vincristine. By potentially avoiding systemic toxic effects of vincristine, MAG demonstrates potential as an inhibitor of neural regeneration for patients with synkinesis. LEVEL OF EVIDENCE: NA.